The Association Between Gadget Use, Physical Activity, and Overnutrition Among Adolescents: A Cross-Sectional Study in Bekasi, Indonesia - Sari, Naadiyah Khofifah; Nur Sartikah, Arindah (CV. Dyoqu Publishing Management, 2025)
Background: Overnutrition among adolescents has become a growing public health concern in many urban regions of Indonesia. Lifestyle transitions, characterized by decreased physical activity and increased screen time due to gadget use, have contributed to this trend. Adolescents living in metropolitan areas, such as Bekasi, often face greater exposure to sedentary habits, which may elevate their risk of developing nutrition-related disorders. Aims: This study aimed to examine the relationship between gadget use and physical activity with the incidence of overnutrition among adolescents in a junior high school setting in Bekasi, Indonesia. Methods: A cross-sectional analytical observational design was employed with 100 students aged 12–15 years from SMP Negeri 33 Bekasi. Data on gadget usage were collected using a validated questionnaire developed by Khulwia (2018), while physical activity levels were assessed using the Physical Activity Questionnaire for Adolescents (PAQ-A). Nutritional status was determined through anthropometric measurements, with body mass index-for-age z-scores (BMI-for-age) as the reference indicator based on WHO standards. Data were analyzed using the Chi-square test to assess the associations between variables. Results: The analysis showed that 59% of students had high gadget use and 45% engaged in low physical activity. A total of 31% of the respondents were classified as having overnutrition. The Chi-square test revealed no significant association between gadget use and overnutrition (p = 0.452), while a statistically significant relationship was found between physical activity and overnutrition (p = 0.000). Students with lower physical activity levels were more likely to be overnourished compared to those with higher activity levels. Conclusion: The findings highlight that physical inactivity is significantly associated with overnutrition among adolescents, emphasizing the critical role of regular physical activity in maintaining a healthy nutritional status. Although no direct association was found between gadget use and overnutrition, high gadget use may indirectly contribute to a sedentary lifestyle, reinforcing the need for balanced screen time regulations. Public health interventions and school-based programs should prioritize increasing physical activity among adolescents to combat the rising trend of overnutrition in urban areas.